RESPON TIANG DALAM KELOMPOK TERHADAP GAYA LATERAL METODE STRAIN WEDGE - Sumiyati Gunawan; Niken Silmi Surjandari; Bambang Setiawan (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2020)
Calculation of lateral bearing capacity of the foundation becomes very important if lateral loads dominate, for example the foundation on bridges, tall buildings, and tower structures. Pile foundations that receive lateral loads, are generally calculated based on the ability of a single pile even though in its application, pile groups are always used. The carrying capacity of the pile group in lateral direction is not the same as the sum of the carrying capacity of a single pile in a pile group. This is due to the differences in the reduction factor supported by the force, direction of the force, number of piles in the group, position of piles in the group, diameter of the piles, the distance between the piles, stiffness of pile, type and stiffness of the soil. This research will analyze the bearing capacity of the pile group using the strain wedge method in the 1x3 and 3x1 configurations with a round steel pipe with a diameter of D = 0,4 m and a square steel pipe with a width of B = 0,429 m; length varies between L = 8,0 m to L = 20,0 m, 2 m intervals and the ratio of pile distance and diameter S/D = 3, on soft silt sand soils with an inner friction angle of 10o and a weight volume of 1200 kg/m3. The results obtained, in the configuration 1x3 the lateral resistance of the square pile is greater than the circle pile about 2,1 times at all pile positions in the group, with S/D = 3. So if L = 10 m, the interaction between the pile and soil insignificant so that the lateral bearing capacity of each pile is the same as a single pile, the multiplier factor for square and circular piles is almost the same. In the configuration 3x1 the lateral resistance of the square pile is greater than the circle pile about 1,4 times at all pile positions in the group. For piles with length L = 10 m, the multiplier factor of the square pile is greater than the circle pile by 1,07 times at all pile positions in the group, and for L = 10 m, the multiplier for the circle pile is greater than the square pile by 1,04 times in all pile positions in the group.